ENZYMATIC SYNTHESIS OF CELLULOSE PROPIONATE AND ITS POTENCY AS RAW MATERIAL FOR MEMBRANE - Anna Roosdiana; Diah Mardiana; Ellya Indahyanti; Dyah Ayu Oktavianie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
ABSTRACT Modification of bacterial cellulose through enzymatic esterification between cellulose and propionic acid has been carried out to produce cellulose propionate as raw material of dialysis membrane. The research aimed to characterize of cellulose propionate and assess its potency as raw material for membrane. The esterification was performed for 8 hours at 50 ⁰C with cellulose and propionic acid in mass ratio of 1:5. The physical chemical properties of resulted cellulose propionate were determined for functional group using FTIR, crystallinity index by XRD, swelling index by gravimetric method, specific gravity, maximum pore size diameter and membrane thickness. The cellulose propionate showed peak absorbance at wave number of 1743 cm-1 from C=O absorption and 1108 cm-1 and 1037 cm-1 from C-O absorption with degree of crystallinity of 61.56% and density of 1.39 g/cm3. Cellulose propionate membrane has maximum poressize of 2.25 ± 0.04 µm and thickness of 0.029 ±0.001mm, the swelling index of 153%. Diffusion equilibrium of uric acid was 3 hours at average diffusion rate of 1.48ppm/h.Keywords : Bacterial cellulose, cellulose propionate, characteristic, diffusion rate